Determinan Pengungkapan Corporate Social Responsibility : Studi Empiris Pada Perusahaan Makanan Dan Minuman Di BEI - Ika Candra Dewi; Fadilla Cahyaningtyas (Jurnal Penelitian Teori dan Terapan Akuntansi (PETA), 2022)
One of the industries that disclose CSR is food and beverage companies0. Currently, many food and beverage companies are competing to improve and create new food and beverage products, from existing ones being developed to be more unique and varied to creating products that have never existed.This study aims to determine0the effect of firm0size, profitability0and liquidity on CSR. The research population is food and beverage companies0listed on the Indonesia Stock Exchange (IDX) for the period 2018-2020 with a total population of 30 companies. The sampling technique was purposive sampling so as to get a sample of 15 companies. Research data is secondary data. The research data analysis0method used0multiple linear regression analysis using the classical assumption test and the t-test hypothesis test. The results0showed that firm size had a positive effect on CSR, while liquidity profitability had no effect on CSR.